2016
DOI: 10.1128/msphere.00028-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immunomodulatory Flagellin-Like Protein FlaC in Campylobacter jejuni and Other Campylobacterales

Abstract: Flagellins not only are important for bacterial motility but are major bacterial proteins that can modulate host responses via Toll-like receptor 5 (TLR5) or other pattern recognition receptors. Campylobacterales colonizing the intestinal tracts of different host species harbor a gene coding for an unusual flagellin, FlaC, that is not involved in motility but is secreted and possesses a chimeric amino acid sequence composed of TLR5-activating and non-TLR5-activating flagellin sequences. Campylobacter jejuni Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“… Adherent THP-1-luc cell line (monocyte-macrophage-like cells, differentiated state after lentiviral transduction using the Cignal Lenti NFkB Reporter (luciferase) system of SABiosciences/Qiagen;[ 112 ]) were coincubated with H . pylori N6, its isogenic core heptose mutants and the CagT4SS functional negative mutant cagY (HP0527) at an MOI of 25 bacteria per cell for 4 h. IL-8 release into the supernatants was quantitated by ELISA.…”
Section: Supporting Informationmentioning
confidence: 99%
“… Adherent THP-1-luc cell line (monocyte-macrophage-like cells, differentiated state after lentiviral transduction using the Cignal Lenti NFkB Reporter (luciferase) system of SABiosciences/Qiagen;[ 112 ]) were coincubated with H . pylori N6, its isogenic core heptose mutants and the CagT4SS functional negative mutant cagY (HP0527) at an MOI of 25 bacteria per cell for 4 h. IL-8 release into the supernatants was quantitated by ELISA.…”
Section: Supporting Informationmentioning
confidence: 99%
“…The flagellum is composed of two types of flagellin including FlaA (1530 nucleotides, 53 KDa) and FlaB (54 KDa) (YAN et al, 2003;SADEGHI and DOOSTI, 2017). Amino acid homology between flaA and flaB subtypes is 58% identical and both genes are essential for the full motility and sustainability of the contamination in gastric mucosa (FABER et al, 2016). FlaB is a larger and scattered strand protein exclusively near the source.…”
mentioning
confidence: 99%
“…However, the absence of these genes may affect the ability of C. jejuni to invade into epithelial cells as flaA is essential for invasion into such cells and responsible for adherence to them (Jain et al, 2008). The absence of flaC may also effect invasion and adhesion as Faber et al, found that flaC is a secreted effector flagellin which may help to modulate the immune response and invasion into epithelial cells (Faber et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another protein, FlaC, is highly conserved among C. jejuni strains and its gene was thought originally to be a third flagellin based on amino acid carboxy region similarities with FlaA and FlaB (Faber et al, 2015;Guerry, 2007). FlaC also requires a flagellar structure to be present before it can be secreted and has been proposed to act as a secreted effector protein which modulates the immune response in the intestinal tract and may contribute to the persistence of the Campylobacter in the gut (Faber et al, 2015). The two other flagellin genes, flaA and flaB, are arranged in tandem.…”
Section: Motilitymentioning
confidence: 99%
See 1 more Smart Citation